Gender Differences in Triggers of Stimulant Use Based on the National Survey of Prisoners in Japan. (2nd January 2021) - Kondo, Ayumi; Shimane, Takuya; Takahashi, Masaru; Takeshita, Yoshiko; Kobayashi, Michiko; Takagishi, Yuriko; Omiya, Soichiro; Takano, Youichi; Yamaki, Mayuko; Matsumoto, Toshihiko
Abstract: Background: There are a few studies on gender differences in terms of reasons and motives for methamphetamine use. Purpose/Objectives: To examine gender differences in triggers of methamphetamine use Methods: We provided a questionnaire survey to 699 inmates who were incarcerated because of violation of the Stimulants Control Act. Results: The results of DAST-20 (the severity of drug dependence) moderately correlated with the applicable numbers of the 37 situational triggers and 34 emotional triggers for stimulant use, respectively. Regarding gender differences, items including "when having sex" [46.3% (men) vs. 25.3% (women)], "when I have some money" (39.4% vs. 25.3%), and "after getting paid from work" (22.1% vs. 11.4%) were applicable in a significantly higher proportion in males ( p  < 0.001 and p  = 0.008, respectively), whereas items including "worried about the body shape" (3.5% vs. 31.2%) and "after quarreling with someone" (11.7% vs. 29.1%) were applicable in a significantly higher proportion in females ( p  < 0.001 for both comparisons). Further, most trigger (emotions) items that exhibited gender differences were significantly higher in females. Many females answered that they had used drugs to relieve discomfort symptoms associated with menstrual periods. Conclusions/Importance: Thus, the awareness of important factors including learning how to deal with negative emotions (e.g. depression), repairing self-image, and recognizing physical and emotional changes associated with the menstrual cycle is helpful in providing proper care and treatment of drug addiction in females.